Analysis of Factors Influencing Employment Opportunities in the Provinces of Sumatra Island: Analisis Faktor-Faktor Yang Mempengaruhi Kesempatan Kerja Di Provinsi-Provinsi Pulau Sumatera - Ariel Siswantoro; Parwito Parwito; Harry Yanza Putra (Gayaku Publisher, 2026)
Employment opportunities are one of the key indicators of successful economic development because they are closely associated with economic growth, income distribution, and social welfare. Differences in regional economic performance across the provinces of Sumatra Island have resulted in varying capacities to generate employment. This study aims to examine the effects of Gross Regional Domestic Product (GRDP), investment, and Provincial Minimum Wage (PMW) on employment opportunities in ten provinces of Sumatra during the 2019-2024 period. The study employs a quantitative approach using panel data obtained from Statistics Indonesia (BPS). Panel data regression analysis was conducted by estimating the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), while the Chow and Hausman tests were used to determine the most appropriate estimation model. The empirical results indicate that the Fixed Effect Model is the most suitable model for the analysis. Partially, GRDP has a positive and statistically significant effect on employment opportunities, indicating that higher regional economic output increases labor demand. Investment also has a positive effect on employment by expanding production capacity and creating new job opportunities. In contrast, the Provincial Minimum Wage has a positive but statistically insignificant effect, suggesting that wage adjustments during the study period did not substantially affect employment absorption. Simultaneously, GRDP, investment, and PMW significantly influence employment opportunities, with the model explaining approximately 66.96% of the variation in employment across provinces. These findings imply that sustainable economic growth and productive investment are essential drivers of employment creation in Sumatra. Therefore, policymakers should promote labor-intensive investment, strengthen regional economic competitiveness, and formulate balanced wage policies that improve workers' welfare while maintaining business sustainability and employment growth.